Strategi Kompetensi Kewirausahaan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar - Silfia Andriani; Rahmatullah Rahmatullah; Siti Mayang Sari (Faculty of Social Science, Universitas Negeri Padang, 2026)
This study aims to analyze the entrepreneurial competency strategies of school principals in improving the quality of education at the elementary school level. The research was conducted at SDN Lubuk Layu using a qualitative approach through observation, interviews, and documentation techniques. Data analysis was carried out using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach, followed by the preparation of IFAS and EFAS matrices to identify internal and external factors influencing the implementation of the principal’s entrepreneurial competencies. The results show that the principal possesses several key strengths, including the ability to innovate in developing school programs, the ability to motivate teachers to innovate in the learning process, and the ability to build cooperation with the community, school committees, and other related stakeholders. Other supporting factors include support from teachers and parents, as well as opportunities for collaboration with government institutions and other organizations. However, several challenges were also identified, such as limited budget, inadequate facilities and infrastructure, high administrative workload, and resistance to change from some members of the school community. The IFAS analysis indicates that the internal condition of the school is relatively strong, while the EFAS analysis shows that there are considerable external opportunities to support school development. Based on the SWOT analysis, several strategies can be implemented, including the development of innovative programs based on school needs, increasing community participation, utilizing technology in the learning process, and strengthening cooperation networks with various stakeholders. This study concludes that the entrepreneurial competence of school principals has a significant contribution to creating educational innovation, strengthening collaboration between schools and the community, and improving the quality of education sustainably.